(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
The present study was conducted to assess the feasibility of hydrogen peroxide (H2O2) for milk preservation and also to investigate the effects of H2O2 on growth of bacteria population in milk. Milk samples were collected from Bangladesh Agricultural University dairy farm and preserved with 0.12% H2O2 of 10% concentration on the basis of volume of milk and milk without H2O2 addition treated as control sample. Parameters used to monitor the shelf life of milk were organoleptic and chemical tests. All milk samples were kept in glass container at room temperature (28-31°C) in the laboratory. Organoleptic parameters (color, flavor, texture, taste) and chemical tests (acidity %, COB test and pH) were done every one hour interval until spoilage. Standard Plate Count (SPC) of the samples was done two times, initially and after spoilage of milk. Acidity% increased gradually in all sample but this increase was rapid in control sample than H2O2 treated sample. From COB test it was found that raw milk sample gave positive result at 10th hour but 0.12% H2O2 treated sample (after 20 min of milking ) and 0.12% H2O2 treated sample (after 3 hrs. of milking ) gave positive result 14 and 15th hour respectively. From the result it was observed that shelf life of milk with H2O2 increased. From the SPC result it was found that the bacterial growth rate is very high in control milk sample compare to H2O2 treated milk sample. Significant difference (p<0.01 was found in case of bacterial growth rate of the milk samples. The results of this experiment indicated that H2O2 be used as an effective preservative for prolonging milk preservation. So H2O2 can be used as an effective milk preservative for prolonging milk storage in environmental condition. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (1), 19-25